Giardia intestinalis assemblage E as an Emerging Zoonosis in Livestock - April Hari Wardhana (Indonesian Center for Animal Research and Development, 2017)
Giardia intestinalis is a gastrointestinal parasite causing giardiasis that infects animals and humans. Giardiasis generates diarrhea, malabsorption, decreased body weight and milk production, dehydration, and mortality especially in young animals. This paper describes G. intestinalis assemblage E in humans and livestock, including molecular identification and disease distribution. The incidence of giardiasis in humans and livestock has been reported in some countries, particularly in young host living under poor sanitation and hygiene. Based on genotype, the parasite is divided into eight assemblages (A-H) and some infect specific hosts. At the moment, assemblage E is known as genotype that infects animal. This statement is controversial since assemblage E was also detected in humans who contacted with animals. This condition assumes that assemblage E is an emerging zoonosis that needs special attention.